Comparative Study to Assess the Level of Anxiety Among the Patients Undergoing Bronchoscopy and Cardiac Catheterization - Kaur, Rupinder; Kansal, Neha; Mehmi, Rinku; Sidana, Ajeet; Pal, Rajni; Kaur, Ramanpreet; Rashika; Kaur, Ravneet; Rubal (Innovational: Journal of Nursing and Healthcare, 2024)
Aim: A comparative study was done to assess, compare, and finding an association between the level of anxiety among patients before undergoing Cardiac catheterization and Bronchoscopy and selected socio-demographic variables. Methods: A total of 100 samples (50 from Cardiac Catheterization Unit [CCU] and 50 from bronchoscopy) both males and females of age >18 years were selected using simple random sampling technique from CCU and Pulmonary Medicine Ward, Bronchoscopy Unit of Government Medical College and Hospital, Chandigarh. The samples were selected using point prevalence. The tool consisted of two parts: Part A: Socio-demographic profile including gender, age, marital status, education, occupation, and religion and Part B: Hamilton Anxiety Rating scale. Interview technique was used to collect data. Descriptive (frequency and percentage) and inferential (Chi-square) statistics were used to compare and find association between levels of anxiety between socio-demographic variables and levels of anxiety. Results: The results showed that in patients undergoing angiography, 90% of them had mild anxiety, 10% had moderate anxiety and none of them had severe anxiety, whereas compared to patients undergoing bronchoscopy, out of 50 patients 50% of them have mild anxiety, 22% have mild to moderate anxiety and 28% of them have mild to severe anxiety. Statistically significant comparison was found between levels of anxiety in patients undergoing angiography and bronchoscopy. No statistically significant association was found between selected socio-demographic variables and the levels of anxiety in patients undergoing angiography and bronchoscopy. Conclusion: The study concluded that statistically significant comparison was found between levels of anxiety in patients undergoing angiography and bronchoscopy.